(untitled) - Yeates, Maurice (New York, 1989)
Provides an overview of the broad scope of the geographer's contributions to the study of urban area. The 3 parts cover: North American urban systems, Internal structure of urban areas, and Improving livability in urban North America
Keywords: Cities and towns; North america